The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00784-017-2212-1
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal screening and referral behaviour of general dental practitioners in Flanders

Abstract: It is encouraging that 92% of the Flemish general dental practitioners use a probe when screening for periodontitis. However, DPSI is mainly used by younger dentists. An effort should be made to encourage all dentists to use this, so that in every patient, periodontitis can be detected timely, securing the best treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…The data collected concerned some general characteristics of patients with DS, their oral health, their overall health, treatments performed, their oral health behavior, and their behavior during treatment. As to oral health, the most recent scores of patients, measured using the Dutch Periodontal Screening Index (DPSI) in 2012, 2013, or 2014, were included if they were present (Table ) . To the patients whose recent DPSI score was unknown, the evaluating dentists awarded a DPSI score using an estimate based on X‐rays, old DPSI scores, and the dentist/dental hygienist's report.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…The data collected concerned some general characteristics of patients with DS, their oral health, their overall health, treatments performed, their oral health behavior, and their behavior during treatment. As to oral health, the most recent scores of patients, measured using the Dutch Periodontal Screening Index (DPSI) in 2012, 2013, or 2014, were included if they were present (Table ) . To the patients whose recent DPSI score was unknown, the evaluating dentists awarded a DPSI score using an estimate based on X‐rays, old DPSI scores, and the dentist/dental hygienist's report.…”
Section: Methodssupporting
confidence: 93%
“…As to oral health, the most recent scores of patients, measured using the Dutch Periodontal Screening Index (DPSI) in 2012, 2013, or 2014, were included if they were present (Table 1). 21 To the patients whose recent DPSI score was unknown, the evaluating dentists awarded a DPSI score using an estimate based on X-rays, old DPSI scores, and the dentist/dental hygienist's report. Furthermore, the number of absent dental elements was recorded including cause of absence (caries, periodontitis, agenesis etc.…”
Section: Data Collectionmentioning
confidence: 99%
“…Several methods, including the BPE, CPITN, and PSR, are available to assist dentists in assessing and detecting periodontal disease during routine dental examinations. The participants in this study mostly reported using BPE and CPITN as periodontal screening methods, depending on their personal preferences and training, similar to other studies on periodontal screening [ 12 , 13 , 14 ]. Nearly all tools used for periodontal health screening assess the most severe pocket depth but no further information about the loss of interproximal attachment is assessed.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have been conducted in the past to assess the knowledge, attitude, and practices of GDPs in relation to the diagnosis, management, and referral patterns of gingival and periodontal diseases. [16,17] The referral of patients to a periodontist is influenced by a range of clinical and non-clinical factors.…”
Section: Discussionmentioning
confidence: 99%